Analytical solution of system of differential equations by variational iteration method - Ahmed, Jamshad; Hussain, Faizan (BIBECHANA, 2015)
In this paper, Varitational Iteration Method using He’s Polynomials is used to construct the exact as well as approximate solutions of differential equations. From the obtained numerical results, it has been observed that this proposed technique is very efficient and reliable for the solution of the linear and non-linear system of differential equations. Numerical results and graphical representation reflect the accuracy and effectiveness of the proposed modification. BIBECHANA 13 (2016) 77-86